Winners are driven : - Unser, Bobby (John Wiley & Sons, 2003)
"The basic principles in becoming a world champion automobile racer, successful businessman, and human being are exactly the same principles that must be utilized by anyone in order to attain success. The many examples of good sportsmanship, the emphasis on family, the importance of customers, and good customer relationships are so very important in life today. Unser is a man who has lived his life to the fullest, accomplished so very, very much, and yet been true to his friends, his family, his competitors, and is the epitome of success." Barron Hilton, Chairman, Hilton Hotels